Clinicomorphological Profile of Gastric Polyps in Anatomical Pathology Department, Faculty of Medicine, Universitas Indonesia-Cipto Mangunkusumo Hospital (CMH): A Retrospective Study in Correlation of Long-Term Use of Proton-Pump Inhibitors - Fili Sufangga; Nur Rahadiani; Ening Krisnuhoni; Diah Rini Handjari; Marini Stephanie (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Background: Gastric polyps are mucosal elevation into the lumen, found incidentally during endoscopic examination and generally brings no specific symptoms. Long-term use of proton-pump inhibitors (PPIs) is related to the development of the fundic gland polyp (FGP). This retrospective study was conducted to determine the distribution of gastric polyps in CiptoMangunkusumo Hospital along with histomorphological features and their relation with long-term PPI use.Method: This retrospective review is a descriptive analytic study. Gastric polyp cases were taken consecutively from the archive of the Anatomical Pathology Department, Faculty of Medicine Universitas Indonesia/CiptoMangunkusumo Hospital the period of 2016-2017. Clinical data obtained from patient’s medical records. Statistical analysis was carried out with the IBM ® SPSS version 23 program.Results: Among 83 cases of gastric polyps, there were 66 cases of FGP, 11 cases of inflammatory polyps, 5 cases of hyperplastic polyps, and 1 case of Peutz-Jegher polyp. Long term PPI was used in 40 cases and was related with parietal cell hyperplasia.Conclusion: FGP is the most common type of gastric polyp in the Department of Anatomical Pathology CMH. Long term PPI use was found in half of gastric polyps and was related to parietal cell hyperplasia morphology.